Optimalisasi Literasi Numerasi Siswa SD dalam Meyelesaikan Soal Cerita Perkalian melalui Program Pendampingan Pembelajaran - Zulvia Misykah; Dewi Sartika Panggabean; Ahsani Abdina (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This community service program aims to assist students in analyzing mathematical story problems and transforming them into mathematical models or routine problems that are easier to understand and solve. The program focuses particularly on multiplication-related story problems, which are often difficult for elementary students because they require reading comprehension, logical reasoning, and calculation skills. The methods used in this activity included initial observation, delivery of learning materials, intensive mentoring, guided practice, independent exercises, and evaluation of learning outcomes. The activity was conducted at MIS Karya Shabira School, Kolam Tembung Village, Medan, over nearly ten meetings using a holistic approach that considered students’ literacy abilities and individual learning needs. Seven third-grade students out of 30 students participated intensively in this mentoring program. The results indicate that learning assistance successfully supported students in understanding problem contexts, identifying relevant information, determining appropriate mathematical operations, and solving story problems more accurately. In addition, students became more active during learning activities and showed increased self-confidence because the mentoring process consistently encouraged their participation, discussion, and problem-solving involvement in classroom and daily life situations effectively.